2016
DOI: 10.3201/eid2202.151304
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Epidemic Ebola Virus Disease in Conakry and Surrounding Prefectures, Guinea, 2014–2015

Abstract: The capital and neighboring areas remain a focal point of transmission, requiring continued public health vigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Our study, thus, corroborated the findings by Ansumana et al ( 14 ), who reported that about 20% of individuals who died of EVD at the Ebola Treatment Center at Hastings Police Station in WA, died soon on arrival, meaning they presented for treatment late in the disease. Similar features characterized the outbreaks in the urban settings of Conakry, Guinea and Montserrado County of Liberia that experienced intense and prolonged transmission of EVD during this West African outbreak of Ebola ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 63%
“…Our study, thus, corroborated the findings by Ansumana et al ( 14 ), who reported that about 20% of individuals who died of EVD at the Ebola Treatment Center at Hastings Police Station in WA, died soon on arrival, meaning they presented for treatment late in the disease. Similar features characterized the outbreaks in the urban settings of Conakry, Guinea and Montserrado County of Liberia that experienced intense and prolonged transmission of EVD during this West African outbreak of Ebola ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 63%
“…The World Health Organization reported 199 Ebola infections among the country’s Ebola frontline responders, among whom 55% died [10]. The study site was Conakry, the capital and largest city in Guinea and one of the Ebola epicenters [27].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple case definitions were used during the West Africa EVD epidemic, as exemplified by EVD surveillance in Sierra Leone, Liberia, and Guinea, which each used variations of the suspected case definition ( 9 , 11 – 14 ). A commonly used suspected case definition used in Guinea was developed by the World Health Organization (WHO) ( 15 ).…”
mentioning
confidence: 99%